Risk Assessment in Performance Audit European Union Practice - Temirkhanov, Zh.; Beisenova, L.B.; Nurmukhametov, N. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
This paper analyses one of the integral elements of audit methodology in public sector. Since the risk assessment is part of the audit at any stage it should be constantly reviewed throughout the assurance engagement. As an example of best practice, this article specifically discusses the methodology provided by European Court of Auditors. European Court of Auditors as well as independent Supreme Audit Institutions of European Union countries promote their rich experience in enhancing public accountability and financial management in third countries. The article also pays attention to the risk factors in performance audit context and considers modern risk assessment approaches.